KÜLTÜR MİRASININ KORUNMASINA YÖNELİK MEKÂNSAL BİR DEĞERLENDİRME: ESKİ (GELENEKSEL) ANTAKYA EVLERİNİN FONKSİYONEL DEĞİŞİMİ - (:unkn) unknown (My University, 2017)
Kültür mirası, geçmişe ait maddi ve maddi olmayan zenginliklerin izlerini günümüze taşıyan değerler bütünüdür. Tarihi ve kültürel öneme sahip geleneksel konutlar, bu değerlerin başında gelmektedir. Ülkemizde geleneksel konutların korunmasına yönelik olarak benimsenen yollardan biri, bu konutlara kafe, restoran, dernek, otel, müze ve bunun gibi işlevler kazandırılarak korunmasını ve yeniden kullanımını sağlamaktır. Türkiye'nin Kütahya, Safranbolu, Beypazarı, İbradı, Taraklı gibi birçok şehrinde görülen bu uygulama Antakya'da da görülmektedir. Antakya şehri, antik dönemden günümüze kadar çok farklı medeniyetlere ev sahipliği yapmıştır. Farklı kültürlerin derin izlerini taşıyan şehir, tarihi ve kültürel değerlere sahiptir. Bu değerlerden biri de yaklaşık 200 yıllık bir geçmişe sahip Antakya evleridir. Son yıllarda geleneksel Antakya evleri, gerek resmi ve yarı resmi kurumlar, gerekse sivil halk tarafından satın alınarak konut işlevi dışında kafe, restoran ve otel gibi amaçlarla kullanılmaya başlanmıştır. Bu süreç, 2000'li yıllarda başlamış ve 2010 yılından sonra hız kazanmıştır. Araştırma sahası, Antakya şehrinin kurulduğu, Asi Nehri ile Habib-i Neccar Dağı arasında yer alan ve Eski Antakya olarak isimlendirilen mevkidedir. Bu sahada koruma altına alınmış olan toplam 355 konuttan 63 tanesi işlevsel dönüşüme uğramıştır. Araştırma sahası içerisindeki mahallelerden Ulucami, Zenginler ve Güllübahçe Mahalleleri, konutların işlevsel dönüşümlerinin en yoğun olduğu alanlardır. Bu üç mahallede toplam 38 geleneksel konut işlevsel dönüşüme uğramıştır. Günümüzde, koruma altına alınmış olan geleneksel Antakya evlerinin çoğunda, satılık veya kiralık ilanlarına sıkça rastlanılması, fonksiyonel dönüşümün daha da artabileceğini göstermektedir. Bu dönüşümün sağlıklı bir şekilde sürmesi, tarihi evlerin korunabilmesi, gelecek nesillere aktarılması hem tanıtımı ve milli kültürün korunması hem de turizm açısından oldukça önemlidir

Cultural heritage is the whole of the values that convey the traces of material and unmaterial riches of the past to today. Traditional houses having historical and cultural importance are at the leading of these values. One of the ways adopted in our country for the protection of traditional houses is to protect and reuse these houses by providing functions such as cafes, restaurants, associations, hotels, museums and so on. This practice which is seen in many cities of Turkey such as Kütahya, Safranbolu, Beypazarı, İbradı, Taraklı is also seen in Antakya. Antakya city has hosted to many civilizations from antiquity to today. The city, which has deep traces of different cultures, has historical and cultural values. One of these values is the Antakya houses, which have a history of nearly 200 years. Inrecent years, traditional Antakya houses have been bought by both official and semi-official institutions and by civilian people and have been used for purposes such as cafes, restaurants and hotels outside the housing function. This process has begun in the 2000s and accelerated after 2010. The research area is located between the Asi River and the Habib-i Neccar Mountain. Antakya city was built in this area that is called Old Antakya. Of the total 355 houses protected in this area, 63 have undergone functional transformation. Ulucami, Zenginler and Güllübahçe neighborhoods are the areas where the functional transformations of houses are most concentrated. In these three neighborhoods 38 traditional houses have undergone functional transformation. Today, advertisements for sale/rent in the majority of these protected houses indicate that the functional transformation may further increase. It is very important for this transformation to continue in a healthy way, to protect historical houses, to transfer them to future generations, both in terms of promotion and preservation of national cultures and tourism Antakya is one of the important cities of Hatay Province, located in the Adana region of the Mediterranean region in the south of Turkey. Antakya's strategic position on the threshold of the Amanos Mountains, rising between Mesopotamia and the plains of Adana, has made the city important in every period of history. For this reason, the city has become a settlement that has been dominated by many different civilizations from antiquity to today and has been mixed with the historical and cultural values of these civilizations. The oldest settlement of Antakya is located between the Asi River and the Habib-i Neccar Mountain and it is called Old Antakya. Because of this, structures with historical and cultural importance are more often found in this area. Antakya preserved its spatial limits in great measure up to the 19th century, and after the 19th century it showed a spatial development towards the west side of the Asi River. After 1950's years, the city began to spread rapidly to the north, south and west, along with the population moving from the rural areas. This situation caused the population living in the traditional houses between Asi River and Habib-i Neccar Mountain to settle in the modern houses of the new development areas. Thus, traditional houses are transformed into neglected, destructed, or abandoned structures that have been living lower income groups. However, in recent years, these houses have been taken under protection in order to revive the historical and cultural significance of the traditional Antakya houses and to draw attention to the precaution that the houses carry from the cultural heritage standpoint. A way that is observed in our country in the protection of the structures which are historical importance is indirect protection of these structures by making functional transformations on the mentioned structures. The splendid ones are usually allocated to official or semiofficial institutions, while some are purchased by civilian citizens. This situation, which is seen in many of our cities, is also seen in Antakya. In this study, the functional changes of traditional houses, which are seen historically and culturally valuable in Antakya and protected since 1975, have been examined. In recent years, functional changes have been taking place in Antakya's traditional houses in order to provide large-scale conservation, regulatory anxiety and functional features. This situation is important in terms of protection of cultural heritage. For this purpose, traditional houses have been using in different forms such as especially cafes, associations, restaurants, restaurants, etc. These functional transformations of the houses have provided the development of tourism and recreational activities. In this article, firstly literature search has been done and also articles, books, thesis, plans, projects, reports and historical documents about research field and topic have been examined. The current situation of the protected buildings has been researched and the houses which have undergone functional changes have been determined by the field studies. In order to carry out the fields studies more regularly, a zoning plan for protection of 1/1000 scale has been taken from Hatay Metropolitan Municipality Protection and Application Inspection Directorate. This map has been redrawn with the Geographic Information Systems ArcGIS10.1 program. The current state of the protected structures and the houses which have undergone functional change in these structures are shown on the map. The research site is located between the Asi River and the Habib-i Neccar Mountain, which is called Old Antakya, where the city was founded. For this reason, Old Antioch is a field that reflects the historical and cultural values of the city and reveals the traces of the past in a concrete way. There are many historic and cultural buildings, from traditional houses to fountains, from baths to covered bazaars, from historic mosques to synagogues and churches.It is noteworthy that most of the protected structures in the Research Area consist of houses. The number of houses in the research area is 292. On the other hand, there are 51 religious facilities, 25 cafés, 19 commercial centers, 16 fountains, 15 associations, 14 accommodation facilities, 10 residential and commercial buildings, 6 restaurants, 5 educational facilities, 5 official buildings, 5 inns and 5 hammams in this area. In addition, museums, covered bazaars, guest house, water depot, old factory, old police station, such as buildings have been taken under protection. Of the 484 protected structures in the study area, 63 are made up of traditional Antakya houses that have been functionally altered. 24 cafés, 15 associations, 14 hotels and pensions, 6 restaurants have been created with functional transformations of these houses. Apart from these, there are 1 functional arts workshop, 1 beauty salon, 1 abbreviation and 1 guest house, which have undergone functional transformation. When we look at the spatial distribution of the houses that have undergone functional transformation, it is noteworthy that the majority (44 of them) are concentrated between the Asi River and Kurtuluş Avenue. Of these 44 functionally converted houses, 38 are located between the Kemalpaşa Street, Kurtuluş Street and Saray Street trinities. One of the most striking features of this area is that in recent years many traditional Antakya houses have begun to be converted into cafes. Nowadays, the number of establishments in this area that serve as café is 18. These functional transformations of the houses have provided the development of tourism and recreational activities. The functional transformation process of the protected structures in Antakya has been mostly on Kurtuluş Street-Kemalpaşa Street-Saray Street triangle. The main reasons for this are; this area is located in the center of the city, the services such as classrooms, study centers, stores in Saray Street which can especially appeal to the young population are taking place and many streets and streets are opened to traditional Antakya houses. In addition, the widespread use of mansion houses where functional conversion can be done in this area is another important influence. The process of functional transformation of traditional Antakya houses has begun in the early 2000s. Since 2010, every year, cafes, hotels, restaurants, commercial enterprises and associations have begun to provide services one after another. Some tradesmen have indicated on their signboards that commercial enterprises have been converted from traditional houses in order to draw attention to functional transformations. Other businesses have seen the commercial profitability of cafes, hotels, restaurants etc. which have been transformed from traditional houses, and they have started to buy/sale traditional house. In particular, they have set up their own businesses by buying or renting houses that are still in ruins. Others have established more than one business. This situation caused high increases in the prices of the traditional Antakya houses located on Kurtuluş Street, Saray Street and Kemalpasa Street triangle. It is noteworthy that many Antakya houses, which are in disrepair have rental and sale advertisements. Therefore, this indicates that the functional transformations in traditional Antakya houses will continue to increase.
A SPATIAL EVALUATION FOR THE PROTECTION OF CULTURAL HERITAGE: THE FUNCTIONAL CHANGE OF THE OLD (TRADITONAL) ANTAKYA HOUSES